2020
DOI: 10.1155/2020/9875636
|View full text |Cite
|
Sign up to set email alerts
|

ciRS‐7 Promotes the Proliferation and Migration of Papillary Thyroid Cancer by Negatively Regulating the miR‐7/Epidermal Growth Factor Receptor Axis

Abstract: Purpose. The incidence of papillary thyroid cancer (PTC) is increasing, and traditional diagnostic methods are unsatisfactory. Therefore, identifying novel prognostic markers is very important. ciRS-7 has been found to play an important role in many cancers, but its role in PTC has not been reported. This study was performed to evaluate the biological role and mechanism of ciRS-7 in PTC. Material and Methods. The expression of ciRS-7 in PTC tissues and the matched adjacent tissues was determined by quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Only several of them were statistically downregulated after miRNA transfection in both cell lines. Interestingly, a lot of modulated mRNAs in our miR-7-5p transfected cells were already known to be targeted by miR-7-5p in thyroid or other tissues, including EGFR, IGF1R, IRS1, IRS2, RAF1, PI3K, MNK1, MNK2 ( Figure 3 ) [ 19 21 , 36 , 41 45 ]. Our approach thus allowed us to get an enlarged and precise vision of the regulation exerted by miR-7-5p in a thyroid context.…”
Section: Discussionmentioning
confidence: 99%
“…Only several of them were statistically downregulated after miRNA transfection in both cell lines. Interestingly, a lot of modulated mRNAs in our miR-7-5p transfected cells were already known to be targeted by miR-7-5p in thyroid or other tissues, including EGFR, IGF1R, IRS1, IRS2, RAF1, PI3K, MNK1, MNK2 ( Figure 3 ) [ 19 21 , 36 , 41 45 ]. Our approach thus allowed us to get an enlarged and precise vision of the regulation exerted by miR-7-5p in a thyroid context.…”
Section: Discussionmentioning
confidence: 99%
“…In PTc cells with high expression of circ_102002, the expression of E-cadherin was downregulated and the expression of N-cadherin and mesenchymal phenotypic markers was upregulated, while PTc cells with low expression of circ_102002 produced the opposite result (82). cIRS-7 had a similar effect: E-cadherin was downregulated in PTc cells with high expression of cIRS-7, while vimentin levels were significantly increased (83). Similarly, another study suggested that circ_0067934 may promote Tc by regulating EMT and PI3K/AKT signaling pathways (84).…”
Section: Regulation Of Invasiveness By Circrnasmentioning
confidence: 95%
“…The circRNA ciRS‐7 has been found to take part in the development of different diseases 57‐60 . For example, Han and colleagues demonstrated that ciRS‐7 induced migration and growth through modulating the miR‐7‐EGFR axis in papillary thyroid cancer 61 . Zhang and colleagues also showed that ciRS‐7 enhanced epithelial‐mesenchymal transition through sponging miR‐641 to derepress MDM2 and ZEB1 expression 62 .…”
Section: Functions and Mechanisms Of Action Of Newly Discovered Circrnas In Neuropathic Painmentioning
confidence: 99%